Polymer processing - Han, Chang Dae (Rheology and processing of polymeric materials ;, 2007)
Part III: Processing of Thermoplastic Polymers. 15. Flow of Polymeric Liquids in Complex Geometry. 16. Plasticating Single-Screw Extrusion. 17. Morphology Evolution of Immiscible Polymer Blends During Compounding. 18. Compatibilization of Two Immiscible Homopolymers. 19. Wire Coating Extrusion. 20. Fiber Spinning. 21. Tubular Film Blowing. 22. Injection Molding. 23. Coextrusion. 24. Thermoplastic Foam Processing. Part IV: Processing of Thermosets. 25. Reaction Injection Molding. 26. Pultrusion of Thermoset/Fiber Composites. 27. Compression Molding of Thermoset/Fiber Composites.